KONTRIBUSI KAHARUDDIN NASUTION TERHADAP PEMBANGUNAN DAERAH RIAU (1960-1966) - Amalia, Kiki; ', Kamaruddin; ', Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Kaharuddin Nasution was a military man who had served as governorof Riau. Its success in the insurgency in Riau made he was appointed Governor of Riauand replaces SM Amin on January 6, 1960. Methods used ini writing this is a historicalmethod is Heuristic (Collection Source), Verification (Feedback Source), Interpretation,and the last is Historiography (Writing). Heuristic on stage using two authors ismethods references dan methods field. Of research indicates that Kahruddin Nasutionfigures are a society which was instrumental in Riau regional development. At the timeof Governor Riau, he was appointed, he built start of facilities and infrastucture. As forthe construction of is Jalan Sudirman Pekanbaru, Jalan Gajah Mada, JalanDiponegoro, University of Riau, Islamic University of Riau, Mosque An-Nur, DwikoraStadium, and other like. Kaharuddin Nasution known to the public as a highlyidealistic. Not only that, Kaharuddin Nasution also referred to as The Father of RiauArchitecture.Keyword: Contribution, Kaharuddin Nasution, Development, Riau